2016
DOI: 10.1002/jsc.2046
|View full text |Cite
|
Sign up to set email alerts
|

Social Inclusion through ICT: Identifying and Overcoming Barriers to ICT Use

Abstract: Creative approaches to ICT training and development can help to overcome barriers to ICT adoption and usage, leading to increased social inclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…The first relates to motivating the elderly to use new technology by influencing their attitudes towards personal youthfulness and self-efficacy. This can be encouraged through social policies regarding lifelong education as this has the potential to enable the elderly to develop not only ICT skills [54] but also greater youthfulness or juvenescence [55]. Education may also assist in maintaining their intellectual curiosity to learn something new as well as improve their employability in a later career (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The first relates to motivating the elderly to use new technology by influencing their attitudes towards personal youthfulness and self-efficacy. This can be encouraged through social policies regarding lifelong education as this has the potential to enable the elderly to develop not only ICT skills [54] but also greater youthfulness or juvenescence [55]. Education may also assist in maintaining their intellectual curiosity to learn something new as well as improve their employability in a later career (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study by Ferri and Favalli [10] EU policies and rules were examined related to digital literacy and the authors argued that the Internet "has the potential to foster social inclusion of people with disabilities" (p.1), but that "the situation for people with disabilities remains challenging in terms of access to new technologies, and in particular websites and other online services" (p.14). Other studies come to similar results [e.g., 34,35]. Another common type of study is to look at different socio-demographic/economic factors and how they relate to use of e-services.…”
Section: Unit Of Analysismentioning
confidence: 71%
“…In recent years, ICT has been recognized to enhance social inclusion (Choudrie et al, 2017;Taylor & Packham, 2016). Research has found that the use of ICT can enable people to build their social capital, engage in social networks and strengthen their sense of belonging (Urquhart et al, 2008).…”
Section: Social Inclusionmentioning
confidence: 99%